Clinical utility and versatility of the petrous segment of the internal carotid artery in revascularization. (March 2020) - Zaki Ghali, George; George Zaki Ghali, Michael; Zaki Ghali, Emil; Lahiff, Marshall; Coon, Alexander
Highlights: Cervicopetrous ICA bypass proves effective in the treatment of aneurysms of the high cervical ICA. An extradural subtemporal approach is used to access the petrous segment of the ICA. Venous graft is alternately tunneled subcutaneously or in situ through the cervical ICA. Maxillary or middle meningeal arteries may also serve as donors to the petrous ICA. Petrous ICA may be used as a donor to supraclinoid ICA and MCA in revascularization procedures. Abstract: Direct approaches to high cervical lesions, including tumors and aneurysms, carry significant risks. This renders alternative approaches desirable, with vascular disease amenable to exclusion and revascularization to the intracranial circulation, including the petrous or supraclinoid segments of the internal carotid artery (ICA). The cervicopetrous ICA bypass via saphenous venous grafting has proven an effective strategy for treating and excluding these lesions. In current practice, this is performed via an extradural subtemporal approach to access the petrous segment of the ICA and a cervical incision for access to the cervical ICA. The venous graft is alternately tunneled subcutaneously or in situ through the cervical ICA, with the latter eschewing external compression, kinking, and torsion, which increases risk of graft thrombosis with the former. Maxillary or middle meningeal arteries may also serve as donors to the petrous ICA. Moreover, the petrous ICA may be used as a donor in revascularization procedures, to the supraclinoid segment of the ICA and the middle cerebral artery, with petrous supraclinoid and petrous-MCA bypasses described. Clinical utility and operative approaches bypassing to or from the petrous ICA in revascularization procedures are reviewed and discussed.